Is There Imminent Expectation in 1 Thess 4:13–18?: Reconsidering Paul’s Syntax - Gathercole, Simon J. (Novum Testamentum, 2024)
This article will question the conventional view according to which 1 Thess 4:13–18 shows evidence of Paul’s Naherwartung. Although Paul’s expectation of an imminent end is usually assumed to be the default interpretation of 1 Thess 4:15, 17, it actually rests on certain presuppositions about the Greek syntax of these verses in two respects. First, the usual interpretation assumes εἰς τὴν παρουσίαν τοῦ κυρίου as functioning a certain way, although an alternative is equally possible. Secondly, a family of related alternative interpretations understands “who are left (to the Lord’s parousia)” as modifying “we, the living” in some sort of limiting way. After disentangling the proposed alternatives and evaluating the component interpretations, the article will show that there are in fact several plausible interpretations of 1 Thess 4:15, 17, of which the Naherwartung view is only one.